The night librarian - Lincoln, Christopher, 1952- (New York : Dial Books for Young Readers, an imprint of Penguin Random House LLC, 2024)
"Two siblings uncover a new world, featuring Night Librarians and characters literally bursting from their favorite books, in this thrilling graphic novel about the magic that libraries hold"--
"The New York Public Library has always been their favorite place, but lately things have gotten weird things like a dragon imprint on the ceiling and a giant beanstalk! It turns out the books are bursting with magic, and suddenly all sorts of villains are escaping from their books and threatening to destroy the whole library. Now it's up to Page and Turner- as well as a mysterious Night Librarian and a motley crew of escaped storybook characters to save this beloved library from destruction before it's too late!"--back cover.
Keywords: Books -- Comic books, strips, etc; Librarians -- Comic books, strips, etc; Libraries -- Comic books, strips, etc; Public libraries -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Siblings -- Comic books, strips, etc; Characters and characteristics in literature -- Comic books, strips, etc; Villains -- Comic books, strips, etc; Fantasy comics; Graphic novels